Knickerbocker : the myth behind New York - Bradley, Elizabeth L., 1973- (Rivergate Books, 2009)
Diedrich Knickerbocker was created in 1809 by a young Washington Irving, who used the character to narrate his classic satire, A History of New York. Bradley's stunning volume offers a surprising and delightful glimpse behind the scenes of New York history, and invites readers into the world of Knickerbocker, the antihero who surprised everyone by becoming the standard-bearer for the city's exceptional sense of self, or what we now call a New York "attitude."